ҚАРАҚАЛПАҚ ТИЛИНДЕГИ ҚОСПА АТЛЫҚЛАРДЫҢ ИМЛАСЫ - Опаева, Р.А. (FAN va JAMIYAT, 2018)
The article deals with the importance of writing. The author of the article gives the opinions of scientists about the spelling priprinciples of writing in the Turkic langunges. There are some examples of what principles are necessary to use in the writing of compound houns.